THE ROLE OF SMALL AND MEDIUM ENTERPRISES IN ECONOMIC DEVELOPMENT - Kalbinur Makhamatalieva (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract Small and medium enterprises (SMEs) constitute the foundational architecture of virtually every economy on the planet. Representing approximately 90 percent of all registered businesses and accounting for over half of global employment, these enterprises occupy a position of indispensable structural significance in the creation of wealth, the distribution of economic opportunity, and the cultivation of innovation. Yet despite their collective weight, SMEs remain persistently underexamined in mainstream economic discourse, which has historically tilted toward the spectacular growth of large multinational corporations. This thesis undertakes a comprehensive investigation into the multi-dimensional role of SMEs in driving economic development across both advanced and emerging economies. Drawing upon data published by the World Bank, the International Labour Organization (ILO), the Organisation for Economic Co-operation and Development (OECD), and the International Finance Corporation (IFC), the study examines five core dimensions of SME contribution: employment generation, GDP output, innovation and technological adoption, poverty alleviation, and regional development. The thesis further identifies the principal challenges that constrain SME growth — with particular emphasis on the financing gap, regulatory burden, and digital adoption divide — and evaluates policy frameworks designed to address these structural impediments. The findings confirm that SMEs are not merely a feature of economic landscapes but an engine of their transformation. Their capacity to absorb labor, generate enterprise, reduce inequality, and adapt to disruption renders them central to the attainment of sustainable development goals. The thesis concludes with a set of evidence-based policy recommendations directed at governments, development banks, and international organizations.